THE STUDENTS’ ERROR IN WRITING ENGLISH AT SMK DIPONEGORO DEPOK SLEMAN YOGYAKARTA IN ACADEMIC YEARS 2015-2016 - Agus Triyogo (Jurnal Perspektif Pendidikan, 2017)
The aim of this research was analysis the students’ error in writing English at SMK DIPONEGORO, Depok, Sleman Yogyakarta. This research done through qualitative research that focused in naturalistic study. The objective in this research was to know the students’ error in writing English. The result found: writing sentence using simple present, two students indicate error in Ignorance of Rule Restriction that categories of error Interlingua transfer. Writing sentence using simple past, categorized Interlingua transfer and four students’ categorized error Rule Restriction, while writing sentence used simple Future, there were two students categorized in Ignorance of Rule Restriction and two students categorized in selecting word. Finally, at the end of this research is the conclusion that describe the result of the study and then suggestion is offered to students especially Indonesian students and teacher special for English teacher.